PENEGAKAN HUKUM TERHADAP PRAKTEK PUNGUTAN LIAR DI JALAN RAYA OLEH MASYARAKAT DIKAITKAN DENGAN PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2012 (STUDI KASUS DI POLRES LANGKAT) - Mulya Hakim Solichin; Alvi Syahrin; Mahmud Mulyadi; Muhammad Ekaputra (Universitas Sumatera Utara, 2018)
ABSTRACT The crime rate at Polres Langkat have been increasing every year. The practice of thuggery such as illegal levies on the highway is one of several factors that cause this increase of the incidence. The action of Polres Langkat against the practice of illegal levies on the highway is applying the Kitab Undang Undang Hukum Pidana (KUHP), Undang Undang, 2009 No. 22 about road traffic and transportation, the implementation is related to Peraturan Mahkamah Agung (PERMA) 2012, No.2 about the adjustment of the criminal acts limit and the amount of penalties in KUHP. This research was conducted with empirical juridical approach applying secondary and primary data. The descriptive analysis method is used in this research through secondary and primary data. At least there 3 obstacles occurred in the effort of the Polres Langkat Those are law enforcement officials, legislation and legal culture of the Langkat district, while the legal impact on the community of the practice of illegal levies is still considered justified. Based on the results of this research it is suggested that the law enforcement officials must understand. The aplicaion of the next PERMA law correctly. The cooperation work among the law inforcement officials, the the goverment and the community should play an active role through supervision, mental, and moral education to give effect detterent so that it can change the mentality of the offender to be better in their attitude. Keywords: Police Roles, Illegal Levies on Highways, legal policies, Crime Justice System.